Productos para el mejoramiento de capacidades de innovación en las empresas. Vigilancia tecnológica (2022)
The degree work proposal consists in carrying out a technological surveillance on the technique status of the tools to improve innovation capacities in companies, as an input for a research project applicable to small and medium-sized enterprises (SMEs).